Grenada : First Review Under the Extended Credit Facility Arrangement and Financing Assurances Review. (IMF Staff Country Reports; Country Report ;, 2014)
EXECUTIVE SUMMARY Extended Credit Facility (ECF) Arrangement: On June 26th, 2014, the Executive Board approved a three-year arrangement for a total amount equivalent to SDR 14.04 million (about USD 21.7 million, 120 percent of quota). The equivalent of SDR 2.04 million was disbursed upon approval of the arrangement. The equivalent of SDR 2 million (about USD 3 million) will be made available upon Executive Board completion of the first review. Recent Developments: The economy is slowly recovering from a protracted recession, but domestic demand remains weak. Financial balance sheets are strained by non- performing loans, private credit continues to contract, and inflation has been negative or low. Growth is expected to remain positive but below potential over the next two years, as private and public balance sheets are repaired. Discussions with creditors on a comprehensive restructuring of public debt have intensified. Program Performance: Policy implementation is off to a good start. The fiscal consolidation is proceeding as programmed and all quantitative performance criteria for the first review were met. Progress has also been made on the structural reform agenda, with two structural benchmarks met or expected to be met, and two to be finalized soon. In particular, the authorities overhauled the public financial management framework, prepared an initial strategy to strengthen weak public institutions and are modernizing the investment promotion framework. First Review: No substantive changes were made to the macroeconomic framework. Discussions focused on the fiscal outlook for 2014-15, and on structural reforms going forward. No changes are proposed to the programmed fiscal targets. Proposed new structural conditionality focuses on a continued strengthening of the fiscal policy framework through implementing regulations, debt management and revenue administration reforms, as well as a framework for sustainable use of receipts under the new citizenship-by-investment program. The program is still in early stages, and implementation risks remain.